Identification of Landslide Susceptibility Level in Buffer Village Lore Lindu National Park Using Scoring Method - Suni, Muhammad Adam; Mappatoba, Cesar Andi; Basoka, Muhammad Darmawan (PT. Riset Press International, 2023)
A landslide is a form of natural phenomenon that often occurs in mountainous and hilly regions with steep up to very steep slopes. Landslides are one of the most dangerous natural hazards and occur frequently in many hilly or mountainous areas, often occurring without warning and causing loss of life and property, marked with movement material of slope-forming materials in the form of rocks, soil, or materials down the slope. This study aimed to identify the distribution of landslide-prone areas in 86 buffer villages in Lore Lindu National Park, Central Sulawesi Province using geographic information system (GIS) based spatial analysis with scoring and overlay. The research parameters consisted of land cover/use, rainfall, elevation, slope, soil type, lithology, and distance from the fault. Identification of vulnerability factors for susceptibility level was determined according to 7 parameters used in the analysis. The results showed that the level of landslide susceptibility in the study area was divided into 3 classes, namely low (85.679,74 ha), moderate (363.184,89 ha), and high (26.888,46 ha). Villages that have a high level of vulnerability are Lempelero, Runde, Sedoa, Tuare, and Tongoa.